1995
DOI: 10.3109/10826089509060737
|View full text |Cite
|
Sign up to set email alerts
|

The Addiction Belief Scale

Abstract: An eighteen-item Addiction Belief Scale (ABS) was developed to assess strength of belief in the disease versus free-will model of addiction (alpha = .91). Factor analysis of the ABS revealed three dimensions to the disease-model controversy of addiction. These include beliefs regarding personal power (subscale alpha = .91, n = 274), dichotomous thinking (subscale alpha = .83, n = 285), and addiction as a way of coping with life (subscale alpha = .47, n = 286). A discussion of scale analysis and suggestions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Schaler (1995) reported strong internal consistency for the ABS (α = .91, standardized item, α = .91, n = 266) and a three-factor structure described as "power" (α = .91, n = 274), "dichotomous thinking" (α = .83, n = 285), and "addiction as a way of coping with life" (α = .47, n = 286). High construct validity was evidenced by a strong negative correlation (r = −.67, p = .01) between respondents' ABS scores and their beliefs about the percentage of individuals able to recover from an addiction without any form of medical or 12-step-type treatment, that is, the stronger their belief in addiction as a disease (higher ABS score), the lower the percentage of individuals they believed are able to recover without treatment.…”
Section: The Addiction Belief Scalementioning
confidence: 95%
See 1 more Smart Citation
“…Schaler (1995) reported strong internal consistency for the ABS (α = .91, standardized item, α = .91, n = 266) and a three-factor structure described as "power" (α = .91, n = 274), "dichotomous thinking" (α = .83, n = 285), and "addiction as a way of coping with life" (α = .47, n = 286). High construct validity was evidenced by a strong negative correlation (r = −.67, p = .01) between respondents' ABS scores and their beliefs about the percentage of individuals able to recover from an addiction without any form of medical or 12-step-type treatment, that is, the stronger their belief in addiction as a disease (higher ABS score), the lower the percentage of individuals they believed are able to recover without treatment.…”
Section: The Addiction Belief Scalementioning
confidence: 95%
“…High construct validity was evidenced by a strong negative correlation (r = −.67, p = .01) between respondents' ABS scores and their beliefs about the percentage of individuals able to recover from an addiction without any form of medical or 12-step-type treatment, that is, the stronger their belief in addiction as a disease (higher ABS score), the lower the percentage of individuals they believed are able to recover without treatment. The full ABS and factorial analysis can be found in the work of Schaler (1995).…”
Section: The Addiction Belief Scalementioning
confidence: 99%
“…Previous study reported that addiction treatment providers in United Kingdom believed that addiction is a way of coping with life [23]. That belief includes items similar as controllable and psychological subscales of IPQ, for example: alcoholics and drug addicts can learn to moderate their drinking or cut down their own drug use and people become addicted to drugs/ alcohol when life is going badly for them [24].…”
Section: Discussionmentioning
confidence: 99%
“…And several studies of alcohol treatment providers (Cunningham et al, 1996;Forman et al, 2001;Thombs and Osborn, 2001) reveal quite varied ''typologies'' and orientations that appear linked in diverse ways to ideas about treatment and recovery. Indeed, Schaler (1995) suggests matching patients and therapists according to their beliefs about clinical problems. Perhaps conflicting attributions between therapists and their patients on measures of blame and control may contribute to conflicts in compliance with treatment plans.…”
Section: Limitationsmentioning
confidence: 99%